Implicit meaning in life: The assessment and construct validity of implicit meaning in life and relations with explicit meaning in life and depression - Huo, Jun-Yu; Wang, Xin-Qiang; Steger, Michael F.; Ge, Ying; Wang, Yin-Cheng; Liu, Ming-Fan; Ye, Bao-Juan (The journal of positive psychology, 2020)
This study aimed to establish a method for assessing implicit meaning in life (MIL), as well as to determine the relationship between implicit MIL and explicit MIL. This study also tested the hypothesis that implicit MIL would moderate the relationship between explicit MIL and depression. The participants were 242 undergraduate university students (120 women) aged between 18 and 23 (M = 19.71, SD = 1.25) years. Implicit MIL was assessed via a standard implicit association test. In addition, participants completed the Chinese version of the Meaning in Life Questionnaire and the Center for Epidemiologic Studies Depression Scale. Structural equation modeling and other methods were used to analyze data. The results showed that implicit MIL demonstrated good validity in the implicit association test. Implicit and explicit MIL were uncorrelated and structurally distinct. In addition, the implicit presence of meaning moderated the relationship between the explicit presence of meaning and depression.